PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Departemen Sewing PT. Muara Krakatau II) - Septian Aji Wijaya; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2020)
One of the most important resources of a company is human resources. So that every company needs to think of ways to improve the performance of employees they have in order to drive the company's progress. One key to improving employee performance is by maintaining employee motivation and job satisfaction. This study aims to determine the effect of work motivation and job satisfaction on the performance of sewing department employees at PT. Krakatau II Estuary. The type of research used is explanatory research. The sampling technique of this study was proportional random sampling techniques 89. Data collection techniques using a questionnaire with a Likert measurement scale. Data analysis method used is regression analysis with the help of SPSS program version 25.0. The results of the study indicate that partially work motivation and job satisfaction affect employee performance positively and significantly with the regression coefficient values on work motivation variables (0.767) and job satisfaction (0.501) . Valuable t-value of work motivation (6,690) and job satisfaction (4,577). Then simultaneously the variables of work motivation and job satisfaction together affect the employee's performance positively and significantly with the multiple regression coefficient values of work motivation (0.663) and job satisfaction (0.144) with the calculated F-value (23.105). Suggestions given to PT. Muara Krakatau II is improving work motivation and job satisfaction due to work motivation and job satisfaction of the sewing department employees of PT. Muara Krakatau II tends to be still low. Improvements to work motivation are primarily related to the willingness of employees to produce products in accordance with predetermined targets and the willingness of employees to complete work faster than specified. While improvements to job satisfaction, namely the compensation provided and company management.